Short term outcomes of Impella in cardiogenic shock: A review and meta-analysis of observational studies. (1st February 2021) - Iannaccone, Mario; Albani, Stefano; Giannini, Francesco; Colangelo, Salvatore; Boccuzzi, Giacomo G.; Garbo, Roberto; Brilakis, Emmanouil S.; D'ascenzo, Fabrizio; de Ferrari, Gaetano Maria; Colombo, Antonio
Abstract: Introduction: The clinical impact of invasive hemodynamic support with Impella in patients with cardiogenic shock (CS) remains to be defined. Method: Only studies including patients treated with Impella in CS were selected. The primary endpoint was short term mortality, while secondary endpoints were major vascular complications and major bleeding. Results: 17 studies and 3933 patients were included in the analysis. Median age was 61.9 (IQR 59.2–63.5) years, CS was mainly related to acute coronary syndrome (ACS): 79.6% (IQR 75.1–79.6). Thirty-day mortality was 47.8% (CI 43.7–52%). Based on metaregression analysis, the Impella 5.0 (point estimate −0.006, 95% CI -0.01 – - 0.02, p  < 0.01) and the Impella CP (point estimate −0.007, 95% CI -0.01 – - 0.03, p < 0.01) devices were related to a higher survival rate, whereas the Impella 2.5 was not. Furthermore, a correlation with reduced mortality was found when Impella was initiated in CS not complicated by cardiac arrest (CA), and before revascularization, (point estimate 0.01, 95% CI 0.002–0.02, p  < 0.01 and point estimate −0.02, 95% CI 0.023–0.01, p  < 0.001 respectively). The vascular complication and major bleeding rate were 7.4% (95% CI 5.6–9.6%) and 15.2% (95% CI 10.7–21%) respectively, and were associated with older age and comorbidities, while the implantation of an Impella CP/2.5 L was associated with fewer complications. Conclusions: Despite the use of Impella the 30 day mortality of CS still remains high. Our data suggest that the use of an Impella CP, initiation of Impella prior to PCI and in patients without cardiac arrest was correlated with outcome improvements. Highlights: Cardiogenic shock 30 day mortality is high despite the use of Impella. A correct patient selection is a fundamental step. Some technical issues such as the use of a CP device or the initiation prior to PCI are correlated with a better outcomes.